Losing contact: The impact of contactless payments on cash usage - Marie-Hélène Felt (Bank of Canada, 2020)
I investigate the impact of contactless credit cards (CTCs) on cash use in Canada, using panel data between 2010 and 2017. I show that ignoring unobserved heterogeneity would lead to overstating the impact of CTCs on cash usage in a linear model. Using finite mixture modelling, I provide evidence of the differential impacts of CTCs on the extensive versus intensive margins of cash usage. I use a two-part model, with an exclusion restriction for better identification, to model both margins separately. I obtain that CTC use negatively influences the intensive margin of cash usage but not its extensive margin. There is no clear evidence of an S-curve pattern in the impact of CTCs on cash usage over the sample period.
Keywords: C33; D12; E41; 330; Bank notes; Digital currencies and fintech; Econometric and statistical methods; Financial services